A Chebyshev Spectral Method for Normal Mode and Parabolic Equation Models in Underwater Acoustics. (20th May 2020) - Tu, Houwang; Wang, Yongxian; Liu, Wei; Ma, Xian; Xiao, Wenbin; Lan, Qiang
Abstract : In this paper, the Chebyshev spectral method is used to solve the normal mode and parabolic equation models of underwater acoustic propagation, and the results of the Chebyshev spectral method and the traditional finite difference method are compared for an ideal fluid waveguide with a constant sound velocity and an ideal fluid waveguide with a deep-sea Munk speed profile. The research shows that, compared with the finite difference method, the Chebyshev spectral method has the advantages of a high computational accuracy and short computational time in underwater acoustic propagation.